Validation of the Student Early Detection of Pornography (EDP) Scale Instrument Using Jamovi - Khairul Bariyyah; Riko Firmansyah; Dwiki Kristianto; Farhana Ulayya Mufidah Kurniawan; Umma Ainun Zahro; Indah Triswahyuning; Nining Maizura; Alief Laili Budiyono (SCHOULID: Indonesian Journal of School Counseling, 2024)
Technological advances make it easier for teenagers to access potentially damaging content, such as pornography, which has a negative impact on their mental and social health. For this reason, media or tools for early detection of pornographic behavior among teenagers are very important, especially for guidance and counseling teachers in providing appropriate services for students. This study aims to test the validity of the e-booklet-based Early Detection of Pornography (EDP) instrument. The research method used was quantitative with Confirmatory Factor Analysis (CFA) carried out on 97 grade 9 students of SMP Negeri 1 Wagir, through quota sampling. The validity of the instrument was assessed by experts, and construct validity was tested through CFA using Jamovi software. The results show adequate fit index values (CFI=0.902, RMSEA=0.0896), with high reliability (Cronbach's α=0.855). This instrument has consistent good results and is able to detect early pornographic behavior among teenagers. With high validity and reliability results, it is hoped that this e-booklet-based EDP instrument will be useful for guidance and counseling teachers for early detection of pornographic behavior among teenagers